2019
DOI: 10.1167/tvst.8.5.6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Optical Coherence Tomography Retinal Segmentation in Neurodegenerative Disease

Abstract: PurposeThis study assessed agreement between an automated spectral-domain optical coherence tomography (SD-OCT) retinal segmentation software and manually corrected segmentation to validate its use in a prospective clinical study of neurodegenerative diseases (NDD).MethodsThe sample comprised 30 subjects with NDD, including vascular cognitive impairment, frontotemporal dementia, Parkinson's disease, and Alzheimer's disease. Macular SD-OCT scans were acquired and segmented using Heidelberg Spectralis. For the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“… 27 30 Importantly, some of these methods have been applied to OCT images from patients with age-related macular degeneration, 18 , 20 , 24 , 27 diabetic retinopathy, 11 , 25 macular telangiectasia type 2, 29 diabetic macular oedema, 13 , 23 , 24 pigment epithelium detachment, 28 glaucoma, 15 , 30 multiple sclerosis 17 , 26 retinitis pigmentosa, 31 and neurodegenerative diseases. 32 These diseases are characterized by variable thinning of the inner retinal layers (e.g., glaucoma and multiple sclerosis), thickening or cystic changes in the nuclear layers (e.g., macular telangiectasia type 2 and diabetic retinopathy) or focal disruption of the retinal pigment epithelium (RPE, e.g., age-related macular degeneration, macular telangiectasia, and pigment epithelium detachment). However, OCT segmentation algorithms have not been investigated in Stargardt disease despite its unique lesions, including outer retinal or subretinal flecks, 33 outer retinal atrophy with or without RPE loss, and variable loss of choroidal architecture disrupting the Bruch's membrane contour, 34 36 which provide challenges for commercial segmentation software.…”
Section: Introductionmentioning
confidence: 99%
“… 27 30 Importantly, some of these methods have been applied to OCT images from patients with age-related macular degeneration, 18 , 20 , 24 , 27 diabetic retinopathy, 11 , 25 macular telangiectasia type 2, 29 diabetic macular oedema, 13 , 23 , 24 pigment epithelium detachment, 28 glaucoma, 15 , 30 multiple sclerosis 17 , 26 retinitis pigmentosa, 31 and neurodegenerative diseases. 32 These diseases are characterized by variable thinning of the inner retinal layers (e.g., glaucoma and multiple sclerosis), thickening or cystic changes in the nuclear layers (e.g., macular telangiectasia type 2 and diabetic retinopathy) or focal disruption of the retinal pigment epithelium (RPE, e.g., age-related macular degeneration, macular telangiectasia, and pigment epithelium detachment). However, OCT segmentation algorithms have not been investigated in Stargardt disease despite its unique lesions, including outer retinal or subretinal flecks, 33 outer retinal atrophy with or without RPE loss, and variable loss of choroidal architecture disrupting the Bruch's membrane contour, 34 36 which provide challenges for commercial segmentation software.…”
Section: Introductionmentioning
confidence: 99%
“…The Ontario Neurodegenerative Research Initiative (ONDRI) is a multi-site prospective cohort study following patients with neurodegenerative diseases including Alzheimer's disease (AD), mild cognitive impairment (MCI), Parkinson's disease (PD), amyotrophic lateral sclerosis (ALS), frontotemporal dementia (FTD), and a vascular patient cohort (VAS) (Farhan et al, 2017). Over the course of 3 years, multiple assessment platforms acquired comprehensive data from the 520 patients including, clinical and demographic assessments, neuroimaging, neuropsychology, genomics, eye movements, retinal layer morphology, gait performance, and neuropathology (Dilliott et al, 2019;Montero-Odasso et al, 2017;Wong et al, 2019). The multi-modal data collected from ONDRI will be used to explore earlier detection, guide development of novel therapy and improving patient care .…”
Section: Introductionmentioning
confidence: 99%
“…While the literature shows that advances in segmentation algorithms have emerged every few years, the algorithms we evaluated have been used in recently published cross‐sectional and longitudinal studies, and these algorithms will likely continue to be used for some time . However, it is remarkable that our study found no errors to manually correct with IRA 3.8.…”
Section: Discussionmentioning
confidence: 92%
“…However, these studies used fully automated segmentation methods without manual correction and looked at only specific or aggregate retinal layer thicknesses. More recently, one report suggested that manual correction of non‐obvious Heidelberg Spectralis segmentation errors is not necessary …”
Section: Introductionmentioning
confidence: 99%